Silver Nanoparticles - Fabrication, Characterization and Applications 2018
DOI: 10.5772/intechopen.75645
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of Nano-toxicity and Safety Profiles of Silver Nanoparticles

Abstract: Nanotoxicology, which is related with toxic potentials of nanoparticles (NPs) and their adverse effects on living organisms and environment, is a sub-branch of toxicology discipline. Nano-toxicity of NPs depends on their doses, unique chemical, and physical properties. Nowadays, silver (Ag) NPs are used in many consumer and scientific applications such as antimicrobial and pharmaceutical applications, water purification systems, textile industry, and food packaging processes. However, the information that abou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
20
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(20 citation statements)
references
References 141 publications
(136 reference statements)
0
20
0
Order By: Relevance
“…Due to their desirable physicochemical properties, antimicrobial effect, and ease of synthesis, silver nanoparticles (AgNPs) have been successfully applied in hygiene products, cosmetics, textiles, toys, food containers, and dietary supplements [1,3]. However, the widespread use of AgNPs has increased the level of human exposure to these nanomaterials, mainly by inhalation, dermal contact, and ingestion [4]. Numerous studies in recent years have shown that AgNPs elicit toxic effects in various tissues, including the nervous system [5][6][7][8], which raises legitimate concerns about their possible impact on human health.…”
Section: Introductionmentioning
confidence: 99%
“…Due to their desirable physicochemical properties, antimicrobial effect, and ease of synthesis, silver nanoparticles (AgNPs) have been successfully applied in hygiene products, cosmetics, textiles, toys, food containers, and dietary supplements [1,3]. However, the widespread use of AgNPs has increased the level of human exposure to these nanomaterials, mainly by inhalation, dermal contact, and ingestion [4]. Numerous studies in recent years have shown that AgNPs elicit toxic effects in various tissues, including the nervous system [5][6][7][8], which raises legitimate concerns about their possible impact on human health.…”
Section: Introductionmentioning
confidence: 99%
“…In the pretrial, the co-incubation time of 45 and 60 min adversely affected the movement of spermatozoa in higher than the selected concentrations for the main trial. Although time and dose are critical factors for NPs’ toxicity, it is considered that many other factors, such as size, shape, surface, stability, physicochemical properties, magnetic activity, and thermal and electrical conductivity of NPs can affect the dynamic of toxicity, contributing to this result [ 28 ]. After that, the NPs were removed, and sperm quality variables and microbial load were evaluated at times relevant (6 to 24 h) to usual ram semen storage for field AI [ 25 ].…”
Section: Discussionmentioning
confidence: 99%
“…However, minute alteration in the physicochemical properties of NPs such as shape, size, charge, crystal structure, surface area, surface functionality, and customization protocol can distinctly change the toxicity profile of any established nano-formulation ( Zhu et al, 2012 ; Jeevanandam et al, 2018 ). Further, dose, duration and route of exposure, and even the type of cell, organ, or organism receiving the NP exposure are also crucial determinants of the extent and type of nanotoxicity ( Park et al, 2010 ; Lankoff et al, 2012 ; Berger et al, 2013 ; Wang et al, 2013 ; Gliga et al, 2014 ; Chen et al, 2015 ; Schmid and Stoeger, 2016 ; Budama-Kilinc et al, 2018 ; Saini and Srivastava, 2018 ). As nanotoxicity is a multifactorial event, therefore, the choice of the evaluation method or model is crucial for proper qualitative or quantitative evaluation.…”
Section: Nanotoxicity Assessment Using the Organoid Modelmentioning
confidence: 99%